Influence of bioregulators and their time of application on growth, yield and economics of coriander (Coriandrum sativum) - Shivran, A.C.; Jat, N.L (Annals of Agricultural Research, 2016)
The influence of boiregulators and their time of application on growth, yield and economics of coriander (Coriandrum sativum L.) was studied during three winter seasons (Rabi) of 2004-05 to 2006- 07 on a loamy sand soil at Agronomy Farm, SKN College of Agriculture, Jobner, Rajasthan. Bioregulators used were NAA @ 50 ppm and Triacontanol (@ 0.5 ml and 1.0 ml/ litre) with three levels of spray viz., one (40 DAS), two (40 and 60 DAS) and three (40, 60 and 80 DAS) along with one absolute control. The treatments were laid-out in factorial randomized block design with three replications. Based on three years study, it was observed that NAA @ 50 ppm recorded maximum plant height (79.7cm), number of branches/plant (6.56), umbels/plant (22.27), seeds/umbel (34.64) and biological yield (3.07 t/ha) which were on par with Triacontanol @ 1.0 and 0.5 ml/lt. The highest umbellets/umbel (6.55), test weight (10.75 g), seed yield (1.47 t/ha), net returns (Rs. 21,804/ha) and benefit : cost ratio (1.45) were recorded with NAA @ 50 ppm which were comparable with Triacontanol @ 1.0 ml/lt, but significantly superior to Triacontanol @ 0.5 ml/lt and water spray. With regard to number of sprays, significantly maximum plant height, number of branches/plant, umbels/plant, seeds/umbel, seed yield (1.42 t/ha), net returns (Rs. 20,210/ha) and benefit : cost ratio (1.33) were recorded with three sprays at 40, 60 and 80 DAS closely followed by two sprays at 40 and 60 DAS over single spray at 40 DAS.